The application of computer and electronic tools during a sports spectacle in volleyball on the example of PlusLiga - Seweryniak, Tomasz (Business Informatics, 2014)
The paper concerns the sports product created during men’s volleyball matches in the Polish professional league (PlusLiga). The objectives of the article are: analysis of the use of computer and electronic tools in a sports product creation process and provide practical guidelines concerning their use in men’s volleyball in order to increase the attractiveness of a sports spectacle. To achieve the goals, documentation analysis and observations were used. The results show a fairly wide range of use of such tools during the games. Additionally, owing to computer science and electronic technologies, it is possible to continue the development of the product offered by PlusLiga
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 4 (34), s. 25-36
Keywords: professional sport; volleyball; sports spectacle; computer tools; electronic tools; sport profesjonalny; piłka siatkowa; widowisko sportowe; narzędzia informatyczne; narzędzia elektroniczne